Phenological Coadaptation Can Stabilize Predator–Prey Dynamics - Mougi, Akihiko (Frontiers in Ecology and Evolution, 2022)
In recent years, phenology—the seasonal timing of biological life cycles—has received increasing attention as climate change threatens to shift phenology. Phenology is crucial to the life cycle of organisms and their interactions with intimate partner species; hence, phenology has important fitness consequences suggesting that phenology can change through adaptive processes caused by species interaction. However, to date, there is limited understanding of how phenological adaptation occurs among interacting species and consequently affects ecological population dynamics. In this study, a phenological predator–prey co-adaptation model was evaluated to determine how adaptive phenological changes occur in prey and predator and how phenological coadaptation affects their coexistence. Population fluctuations tend to decrease and become stabilized when adaptation occurs rapidly. Furthermore, when adaptation is slow, predator–prey dynamics can be stabilized or destabilized depending on the initial difference in phenological timing between species. These results suggest that phenology shaped by slow coevolution can shift with changes in activity timing caused by environmental changes and simultaneously alter the stability of predator–prey dynamics. In contrast, phenology caused by rapid adaptation, such as phenotypic plasticity, may be robust to environmental change and maintain the stability of predator–prey dynamics. Understanding the types of adaptative processes that shape species phenologies may be crucial for predicting the ecological effects of climate change.